Respuesta :

Answer:

true, I hope this will help.

Answer:

[tex]\boxed{\underline{\bf \: True}}[/tex]

Step-by-step explanation:

[tex] \sf \: 6(10 + 5) = 6•10 + 6•5 [/tex]

Check with LHS = RHS rule method.

LHS

[tex]\sf6(10 + 5) \\ \sf = 6(15) \\ \sf = 6 \times 15 \\ \bf = 90[/tex]

RHS

[tex]\sf6•10 + 6•5 \\ \sf = 60 + 30 \\ \bf= 90[/tex]

We can see that both LHS & RHS give [tex]\boxed{\underline{\bf \: 90}}[/tex]as the solution. LHS = RHS. Hence proved.

Answer -> [tex]\boxed{\underline{\bf \: True}}[/tex]

_______________

Hope it helps.

RainbowSalt2222